2004
DOI: 10.1002/pmic.200400915
|View full text |Cite
|
Sign up to set email alerts
|

The Helicobacter pylori CagA protein induces tyrosine dephosphorylation of ezrin

Abstract: Helicobacter pylori is one of the most wide-spread bacterial pathogens and infects the human stomach to cause diseases, such as gastritis, gastric ulceration, and gastric cancer. A major virulence determinant is the H. pylori CagA protein (encoded by the cytotoxin-associated gene A) which is translocated from the bacteria into the cytoplasm of host cells by a type IV secretion system. In the host cell, CagA is phosphorylated on tyrosine residues and induces rearrangements of the actin cytoskeleton. We have pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 41 publications
0
58
0
Order By: Relevance
“…In this regard, it was reported that Src-mediated CagA phosphorylation is followed by a rapid inactivation of Src kinase activity by the binding of CagA to Csk, and then, Src kinase inactivation leads to the dephosphorylation of Src target proteins such as vinculin, ezrin, and cortactin, which are important in the process of regulation of the actin cytoskeleton and focal adhesions. This process contributes to inducing morphological changes of H. pylori-infected cells (18,23,24). Also, it was shown that phosphorylation of cortactin (serine 405) was mediated by ERK1/2 kinases, which might trap activated FAK, leading to a disturbed turnover of focal adhesions and cell elongation morphology (25).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it was reported that Src-mediated CagA phosphorylation is followed by a rapid inactivation of Src kinase activity by the binding of CagA to Csk, and then, Src kinase inactivation leads to the dephosphorylation of Src target proteins such as vinculin, ezrin, and cortactin, which are important in the process of regulation of the actin cytoskeleton and focal adhesions. This process contributes to inducing morphological changes of H. pylori-infected cells (18,23,24). Also, it was shown that phosphorylation of cortactin (serine 405) was mediated by ERK1/2 kinases, which might trap activated FAK, leading to a disturbed turnover of focal adhesions and cell elongation morphology (25).…”
Section: Discussionmentioning
confidence: 99%
“…The Src-mediated phosphorylation of CagA is followed by an inactivation of the catalytic activity of Src kinases resulting in the dephosphorylation of the actin-binding Src substrates ezrin and cortactin (Selbach et al, 2003;Selbach et al, 2004). As Src kinases are rapidly inactivated, the sustained CagA phosphorylation observed in prolonged H. pylori infections must be accomplished by other molecular means (Selbach et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…CagA has been reported to interact with several host cell proteins and to stimulate various signaling processes in the host (25). Moreover, tyrosine-phosphorylated CagA inhibits c-Src, which leads to tyrosine dephosphorylation of the cellular Src substrates cortactin and ezrin (33,35).…”
mentioning
confidence: 99%